2014
DOI: 10.5365/wpsar.2014.5.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Newborn care practices and home-based postnatal newborn care programme – Mewat, Haryana, India, 2013

Abstract: Knowledge-practice gaps existed among mothers counselled by ASHAs. Poor utilization of reproductive and child health services decreased opportunities for ASHA-mother dialogue on safe practices. Recommendations included training ANMs, training TBAs as ASHAs, innovative communication strategies for ASHAs and improved referral system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 14 publications
8
54
4
Order By: Relevance
“…Fathima et al, [10] and Sinha et al, [6] assessed that the 84% mothers and 95% mothers respectively were advised on immunization by ASHA workers, whereas, Bhaisare et al, [5] revealed only 35% mothers and 37% mothers received advice regarding immunization and initiation of breastfeeding respectively from ASHA workers which was very low as compared to present study. This difference might be because Bhaisare et al, [5] conducted the study in a tribal area of Maharashtra It is seen that if health functionaries imparts better knowledge of immunization to mothers that improve immunization coverage [8,9].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Fathima et al, [10] and Sinha et al, [6] assessed that the 84% mothers and 95% mothers respectively were advised on immunization by ASHA workers, whereas, Bhaisare et al, [5] revealed only 35% mothers and 37% mothers received advice regarding immunization and initiation of breastfeeding respectively from ASHA workers which was very low as compared to present study. This difference might be because Bhaisare et al, [5] conducted the study in a tribal area of Maharashtra It is seen that if health functionaries imparts better knowledge of immunization to mothers that improve immunization coverage [8,9].…”
Section: Discussioncontrasting
confidence: 69%
“…The present study assessed that weight and temperature of the baby was recorded correctly by ASHA workers in more than 85% and 73% of babies respectively. Similar assessments were assessed by different studies in our country [5,6,7].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, nearly, one-third of the participants from both the sectors had inadequate knowledge about this component. Another Indian study done in Meerut, Haryana by Sinha et al also reported that the knowledge and skills of health workers were moderate regarding the umbilical cord care [5]. Various studies done worldwide among the postnatal mothers reported the use of some unsafe materials on the newborn's umbilical cord [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…. 13% in Latika Nath Sinha 10 Our study showed that many (21%) of participants were discarding colostrum. This shows that they had less knowledge regarding importance of colostrum like high concentration of proteins & other nutrients, anti infective properties which protect the baby against respiratory & diarrheal diseases 1 .…”
Section: Resultsmentioning
confidence: 94%